A legendary landscape in peril: Land use and land cover change and environmental impacts in the Wulagai River Basin, Inner Mongolia. (1st January 2022) - Shang, Chenwei; Wu, Jianguo
Abstract: The Mongolian Plateau, home to the world's largest contiguous temperate grasslands, has been known for its vast steppe landscapes and legendary history of the Mongol Empire. However, like temperate grasslands elsewhere around the world, the Mongolian steppe landscapes have been severely degraded by increasing human activities during the past several decades. The main objective of this study was to assess the landscape and ecosystem changes in the Wulagai River Basin (WRB) in Inner Mongolia, where China's last intact steppe ecosystem reportedly resides. Using remote sensing data and landscape metrics, we found that, during 1979–2016, WRB lost about 55 % of wetlands, 76 % of shrublands, and 46 % of sandy-land vegetation, with its most dominant vegetation type shifting from meadow steppe to dry steppe for the first time in history. Human land uses continued to intensify: cropland expanded by about 40 %; impervious surface area increased by almost 34 times; and surface coal mining rampaged through the heartland, tearing up vegetation and sucking up water near and far. The WRB landscape became more diverse compositionally (increasing land cover types), more fragmented ecologically (habitat loss and isolation), and more complex geometrically (anthropogenic and natural landscape elements entangled). Damming, mining, and overgrazing were the major direct drivers for the observed environmental changes. Government-sponsored restoration programs have had positive ecological changes across China, but landscape destruction and fragmentation in the Wulagai River Basin have continued. This dire situation demands urgent government policy intervention and stakeholder-involved governance actions to promote the sustainability of this legendary landscape. Graphical abstract: Image 1 Highlights: Human activities have severely transformed the "last intact steppe" in China. Wetland loss and drying trend in vegetation dominated environmental changes. Damming and mining are key drivers for the negative ecological consequences. Regional sustainability requires abandoning damming and mining. Future research needs to focus on wetland and landscape sustainability.